Predictive model to protect satellites from space weather. (2nd April 2013) - Schultz, Colin
Abstract : The Sun is expected to reach solar maximum this year, heralding a peak in sunspot activity and, within a few years, an increase in geomagnetic storms. Within the past decade, the number of satellites in orbit has soared; these satellites form the technological backbone of an industry worth hundreds of billions of dollars per year. As of May 2012, nearly 1000 satellites occupied orbits around the Earth, with the bulk of these in either geosynchronous or low Earth orbits. Many currently active satellites, however, were launched in the past few years and are flying with new technologies that have been as yet untested in the harsh conditions presented by the peak of the solar cycle. Shifts in satellite construction techniques, including a reliance on off‐the‐shelf components rather than those designed to be hardened against radiation, mean that some modern equipment may remain vulnerable to solar activity. What's more, societal dependencies on the information provided by satellites, including the Global Positioning System time stamps used to drive automatic high‐frequency stock market trading, mean that the potential consequences of satellites being damaged by solar activity have increased.